The Khrushchevites : memoirs - Hoxha, Enver, 1908-1985 (Tirana : "8 Nentori" Pub. House, 1980)
"This work, written in 1976, comprises the author's memoirs and personal impressions of his direct meetings and other various contacts with the leaders of the CPSU and the other Communist and Worker's parties during the years 1953-1961".
Translation of: Hrushovianët.
HU OSA 300 - RFE/RL collection
Keywords: Khrushchev, Nikita Sergeevich, -- 1894-1971.; Hoxha, Enver, -- 1908-1985.; Albania -- Foreign relations -- Soviet Union